2021
DOI: 10.3390/cells10071571
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Vitamins K Exert Anti-Inflammatory Effects Dissociated from Their Role as Substrates for Synthesis of Endogenous MK-4 in Murine Macrophages Cell Line

Abstract: Vitamins K exert a range of activities that extend far beyond coagulation and include anti-inflammatory effects, but the mechanisms involved in anti-inflammatory action remain unclear. In the present study, we showed that various forms of exogenous vitamins—K1, K3, K2 (MK-4, MK-5, MK-6 and MK-7)—regulated a wide scope of inflammatory pathways in murine macrophages in vitro, including NOS-2, COX-2, cytokines and MMPs. Moreover, we demonstrated for the first time that macrophages are able to synthesise endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
(114 reference statements)
2
12
0
1
Order By: Relevance
“…The decreased level of COX‐2 indicates good prognosis as COX‐2 triggers inflammation and apoptosis by secreting prostaglandins and thromboxanes and is activated by NFK‐B which is the master regulator of the inflammatory process. This effect correlates with previous studies on vitamin k reporting its role in decreasing COX‐2 expression however, the exact mechanism for this effect remains unclear 49 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The decreased level of COX‐2 indicates good prognosis as COX‐2 triggers inflammation and apoptosis by secreting prostaglandins and thromboxanes and is activated by NFK‐B which is the master regulator of the inflammatory process. This effect correlates with previous studies on vitamin k reporting its role in decreasing COX‐2 expression however, the exact mechanism for this effect remains unclear 49 …”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a significant increase in NF‐κB was detected. These results were reversed by phylloquinone treatment in agreement with previous studies 39,49 . We assume that the ability of phylloquinone to increase NAD+ resulted in increased SIRT‐1 activity by acting as a substrate for NADH: quinone oxidoreductase 1 (NQO1), which is a catalyst that reduces quinone compounds by NADH oxidation 17 .…”
Section: Discussionsupporting
confidence: 88%
“…Studies suggested that vitamin D may affect intestinal epithelium integrity and innate immune barrier function in the involvement of IBD 60 . Emerging studies support that vitamin K1 is involved in immune response and anti‐inflammation 61 and is associated with the protective and promoting role in the intestine 62 . It has been proved that folate plays a role in regulating reactive oxygen species production and reducing oxidative stress by acting directly as an antioxidant 63 .…”
Section: Discussionmentioning
confidence: 99%
“…60 Emerging studies support that vitamin K1 is involved in immune response and anti-inflammation 61 and is associated with the protective and promoting role in the intestine. 62 It has been proved that folate plays a role in regulating reactive oxygen species production and reducing oxidative stress by acting directly as an antioxidant. 63 Vitamin E reduces lipid peroxidation and thus has a significant role in membrane stabilization 64 The main strength of this study is the MR design that incorporated data from large consortia to provide solid genetic evidence for the reported associations.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that vitamin K antagonists (VKA) contribute to cardiovascular damage [ 20 , 21 ] In turn, dietary supplementation with vitamin K is a safe and feasible option for slowing down vascular disease [ 22 ]. Recent evidence points to the protective effect of vitamin K on blood vessels, by reducing inflammation and stress ER [ 23 , 24 ]. Similarly, vitamin K has been observed to play an important role in the protection of immature oligodendrocytes or neurons, which are highly sensitive to oxidative damage.…”
Section: Vitamin K In Cell Biologymentioning
confidence: 99%